STRATEGIES FOR THE PREVENTION AND ERADICATION OF FEMICIDE: LEGAL, INSTITUTIONAL AND SOCIETAL DIMENSIONS, CHALLENGES AND PERSPECTIVES - Ćopić, Sanja; Jovanović, Slađana (Pravni zapisi, 2025)
Femicide is commonly conceptualized and defined as the gender-based or gender-motivated killing of women. It is a global issue, prompting national states to implement legislative, policy and practical measures and actions to address it. The aim of the paper is to analyse current actions for preventing and suppressing femicide and explore some examples of good practice of state responses to this form of crime. The purpose is to underscore the necessity of recognizing femicide as a persistent issue, identify its characteristics and causes, and explore challenges and possible directions for developing effective preventive responses. Particular emphasize is put on femicide in the context of domestic and partner violence, as the most prevalent type of femicide, which occurs within the broader context of structural discrimination and violence against women.
Keywords: Femicide; Feminicide; Gender-Motivated Killing of Women; Domestic Violence; Intimate Partner Violence; Europe